INFLUENCE OF ORAL PIERCING ON THE STATE OF THE DENTAL SYSTEM AT THE STAGES OF TREATMENT BY THE EDGWIZE TECHNIQUE - Иванова, Ольга Павловна; Цурова, Амина Руслановна (Medicine in Kuzbass, 2023)
This article is focused on studying the influence of oral piercing on the dental-jaw system. An integrated assessment of domestic and foreign literature of previous research on this topic was conducted. As well as our own study which included a comprehensive examination of 17 patients with oral piercing, the treatment was carried out using edgewise orthodontic technique. It was determined that oral piercing, in general, has a negative impact on the dental- jaw system. Therefore, it is recommended refrain from piercing during the orthodontic treatment. Then replace the metallic jewelry with acrylic ones and the metal bracket attachments with soft silicone ones. Thus it is possible to achieve minimal traumatic effect of piecing on the soft tissues.
Keywords: oral piercing; complications; dental-jaw system